APOKRYFY NOWEGO TESTAMENTU JAKO INSPIRACJA DLA SZTUKI CHRZEŚCIJAŃSKIEJ: PRZYPADEK IKONOGRAFII PRÓBY GORZKIEJ WODY W ETIOPSKICH ILUMINACJACH - Krawczuk, Marcin Konrad (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
One of the characteristics of Ethiopian Christian art is the presence of motifs which are relatively rare in other areas of the Christian world. An example of such a motif is the ordeal by bitter water which, according to the apocryphal Protoevangelium of James, Mary had to undergo. This scene, which is very rare in early Christian art, appears in ca. dozen Ethiopian illuminations, most of which come from Gospel manuscripts. The Ethiopian iconography of the scene appears to depend on the early Christian prototypes, however certain elements have been added, in particular some symbols connecting the scene to the Jerusalem Temple. This corresponds to the general trend in Ethiopian Mariology to interpret the figure of Mary through the Old Testament. This perhaps was the main reason to include the scene of the ordeal by bitter water to the Ethiopian Marian iconography.